Strategy for the improvement of culture and entrepreneurial spirit in students at the Computer Science School, National University, Costa Rica, 2021 (Revista Electrónica Calidad en la Educación Superior, 2024)
The objective of this research is to define a strategy and an action plan to enhance the culture and entrepreneurial spirit of the students of the School of Informatics of the National University, Costa Rica. The methodology is mixed, combining qualitative and quantitative approaches, as well as an exploration of a non-probabilistic sample composed of 491 students, which represents approximately 33% of the population in 2021. Two specific methods were used: a questionnaire to carry out the initial diagnosis and a focus group to identify the strategic actions to follow. As a result, the student body has little knowledge of entrepreneurship, the scarcity of techniques provided by the university, the need to enhance this competence and increase female participation in fields related to STEAM and entrepreneurship. It is concluded that there must be a roadmap with gradual and quantifiable planned actions, which positively impacts all actors involved in the process.
Keywords: Entrepreneurship; competition; strategy; computing; universities